Role of Reductants, Photosensitizers and Surfactants for Solar Energy Conversion and Storage: EDTA-Azure-A-NaLS System - Gunsaria, R.K.; Hussain, J. (Asian Journal of Chemistry, 2010)
Efforts have been made to prepare some efficient photoglavanic cells using anionic micelles-sodium lauryl sulphate (NaLS), ethylene diamine tetraacetic acid disodium salt (EDTA) as an electron donor and a dye Azure-A as photosensitizer. The photogalvanic cell so prepared shows remarkable electrical output—photopotential 814.0mV, photocurrent 255.0 μA and power of the cell 207.57 μW. The determined conversion efficiency was 1.20% and fill factor was 0.45 where the maximum possible value is 1.0. The current-voltage characteristics have been studied in detail and a tentative mechanism for the photogeneration of current is also proposed.